2011
DOI: 10.1350/ijps.2011.13.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Managers in Suits and Managers in Uniforms: Sources and Outcomes of Occupational Stress

Abstract: Sources and outcomes of occupational stress among police managers are examined on a sample of 267 senior police officers in one The results are then contrasted with those of 232 managers in private industry in the same country. Managers in the private sector work longer hours, report higher impatience (one component of a Type A behaviour pattern), are more internal in locus of control, rely less on social support as a means of coping with stress, and perceive more masculinity, less uncertainty avoidance, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…More studies have been carried out during the last decade to investigate occupational stress. For example, studies found that level of occupational stress differ dramatically among employees due to some workplace factors such as workload, support, resources, control, recognition, person resiliency and compensation (Pagon et al, 2011;Prayogo et al, 2017). These studies argued that occupational stress is related to the negative impact on the well-being of employees in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…More studies have been carried out during the last decade to investigate occupational stress. For example, studies found that level of occupational stress differ dramatically among employees due to some workplace factors such as workload, support, resources, control, recognition, person resiliency and compensation (Pagon et al, 2011;Prayogo et al, 2017). These studies argued that occupational stress is related to the negative impact on the well-being of employees in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…The bureaucratic and quasi-military nature of police organizations tends to limit an individual's ability to exert control over his or her work environment when compared to private-sector employment. Less control is reported to contribute to more perceived work-related pressures among officers concerning issues such as workload, daily work hassles, coworker relations, organizational climate, and recognition (Pagon, Spector, Cooper, & Lobnikar, 2011). Additionally, the hierarchical control structure within the bureaucracy may be most rigid in the largest police departments.…”
mentioning
confidence: 99%
“…However, these authors argue that it is not the sector itself, but the cultural characteristics of the sector that will allow workers to develop and express coping strategies that are specific to public and private organizations. In this sense, in the sector where the organizational culture allows workers to have control, the workers will be able to use active forms of coping (Krajewski & Goffin, 2005;Pagon, Spector, Cooper, & Lobnikar, 2011;Widerszal-Bazyl et al, 2000 ). Public workers in Portugal are the ones that can use this type of strategies according to the cultural characteristics of the sector.…”
Section: Limitaciones Y Pistas Para Futuras Investigacionesmentioning
confidence: 99%